The effect of (S.N.I.p.S) strategy in divergent thinking style in learning the skills of serving and preparing Volleyball for students - حازم علي غازي Imad Azez Nashmie, Assistant (Mustansiriyah Journal of Sports Science, 2024)
Through the researcher being a teacher of volleyball and specializing in teaching methods, he noticed the need to search for a serious strategy and an appropriate method for it for the purpose of involving students in the educational process and moving away from the methods used, which suffice only with indoctrination without challenging the mental abilities and capabilities of students and making them preoccupied with research, investigation and experimentation, so the researcher decided to carry out a study Serious scientific study of this problem through the use of (S.N.I.P.S) strategy in divergent thinking style (solving problems) in learning the skills of serving and preparing volleyball for students. The strategy of S.N.I.P.S)) between the method followed and divergent thinking in learning the skills of serving and preparing volleyball for students. The researcher used the experimental approach in the way of equal groups because it fits the nature of the research problem. Their number is (128) students, either the sample of the Research has been chosen randomly and the distribution of the totals to the control and experimental groups by lottery, the control group was taught by the method used by the teacher and the experimental group was taught by the method of divergent thinking and the strength of each group was (15) students.